MENUMBUHKAN JIWA KEWIRAUSAHAAN: MELALUI PELATIHAN BERBASIS RAMAH LINGKUNGAN DI PAYPI YOGYAKARTA - sofiati sofiati; Linawati Linawati (Universitas Islam Raden Rahmat Malang, 2020)
Abstract One of the efforts to conserve the environment is to manage waste so as not to pollute the environment.The potential for plastic bottle waste and cloth waste at the PAYPI Yogyakarta is abundant but has not created a business opportunity.The purpose of this community serice is to foster an entrepreneurial spirit in the orphanage home through the use of recycling to become products of economic value.The method of implementation through 3 stages,including:a) briefing on enterepreneurship material through tutorials accompanied by discussion and role playing;b)practical training for making accessories;c)mentoring in marketing practices, monitoring and evaluation. The method of recruiting training participants is through the selection of the results of discussion the PAYPI managers. This training participant has the qualifications of human resources who are not technologically illiterate and tough. The number of particpants is 17 people consisting of students and students who live in the PAYPI. The result of the training is the growth of entrepreneurial spirit and marketing skills. Based on the results of mentoring, monitoring and evaluation of product marketing activities,it is necessary to have a sustainability program that will come with yhe theme of on line based cutomer service. Keywords: Environmental preservation,entrepreneurial spirit, skills